Empagliflozin Raises Sodium in SIADH Patient, Enabling Timely Surgery - Abouglila, Kamal; Gatnash, Mouad (Journal of Diabetes and Endocrine Practice, 2024)
Empagliflozin, a selective sodium-glucose cotransporter 2 (SGLT2) inhibitor, induces osmotic diuresis via glucosuria and may represent a novel therapeutic approach for managing syndrome of inappropriate antidiuretic hormone secretion (SIADH). This case report details the successful use of empagliflozin to correct persistent hyponatremia in a 78-year-old man with SIADH, awaiting elective abdominal surgery for hernia repair over several months. The patient, who had a history of hypertension and multinodular thyroid goiter with normal thyroid function tests, continued to experience low serum sodium levels despite discontinuing enalapril, previously used for hypertension management. An extensive evaluation confirmed a diagnosis of SIADH, with sodium levels initially ranging between 124 and 128 mmol/L. Traditional management, including fluid restriction, failed to normalize his sodium levels, leading to repeated cancellations of his scheduled surgery due to persistent hyponatremia. In October 2023, treatment with empagliflozin was initiated, leading to a gradual increase in sodium levels. Within 3 weeks, his serum sodium had normalized to 134 mmol/L, accompanied by a rise in serum osmolality. As a result, the elective surgery was successfully performed without complications. These findings suggest that empagliflozin, in combination with fluid restriction, offers a promising treatment option for improving sodium levels in patients with SIADH, helping avoid unnecessary delays in elective surgical interventions.
Keywords: empagliflozin; SIADH; hyponatremia; SGLT2 inhibitor